Decolonizing Diplomacy: A Systematic Review of Southeast Asian Countries' Diplomacy Strategies - Rahmadian, Faris; Hospes, Otto; Termeer, Katrien (Institute of International Studies, 2025)
Diplomacy has long played a pivotal role in shaping international relations, yet much of the scholarly literature remains Western-centric, often overlooking the rich traditions and histories of non-Western countries. A key yet frequently neglected moment was the 1955 Bandung Conference, where newly independent Asian and African nations asserted their agency on global stage. Championing non-alignment and solidarity, the conference demonstrated that formerly colonized and marginalized people could articulate and define their own approaches to international relations. This paper takes 1955 as a starting point and addresses these gaps by conducting the first-ever systematic literature review of diplomacy strategies in Southeast Asian (SEA) countries. A total of 92 articles were analyzed using the theory of ideational power, alongside an examination of domestic and international factors shaping these strategies. Taken together, SEA countries employ diverse diplomatic strategies, often favoring informal approaches that emphasize neutrality, foster warm sentiments, and create positive atmospheres. At times, they adopt assertive strategies, such as dismissing opposing ideas or referencing historical events to strengthen their position. Another feature of SEA diplomacy is its strategic positioning among global powers and regional organizations, consistently leveraging their stance. These strategies are shaped by a combination of factors, including leadership, cultural and religious identity, colonial legacies, international pressures, and the role of ASEAN. Reflecting on Bandung’s ideals and the role of ideas in SEA countries, this paper advocates for decolonizing diplomacy by challenging Western-centric narratives and promoting a more inclusive, historically informed understanding of diplomatic practices that value diverse perspectives and experiences.Keywords: non-western diplomacy, decolonizing diplomacy, diplomacy strategies, southeast asian diplomacy